The transitional space in the traditional urban settlement of Cyprus - Pulhan, H; Numan, I (Locke Science Publ Co Inc, 2005)
The interactions between public and private, people and environment, open and closed, inside and outside, and part and whole are important design criteria in traditional environments. This interaction and indissoluble whole of the fabric, transitional space, which is described as the overlapping of indoor and outdoor spaces, has great importance. In different cultures, transitional spaces have different names: arcade, engawa, vestibule, eiwan, and hayat. It is commonly named sundurme in Cyprus. Sundurme is the essential component that determines the spatial patterns and formal configurations in the traditional architecture of Cyprus. At the same time, it is the forthcoming transition device between traditional and contemporary environments of Cyprus. Through open and renewed interpretations, sundurme has the potential to be a cultural transition that can achieve continuity of traditional values and maintain physically and socially satisfying environments. Furthermore, any planning and designing strategy that considers the potential of sundurme in new housing developments as a shared image of all communities living on the island could contribute to the sociopolitical process. Under this scope, this study points out the cultural and architectural role of sundurme and describes its spatial, functional, and climatic characteristics by referring to the formal analysis results of 154 houses. The study aims to draw attention to the importance of sundurme in the development of living environments towards achieving better living conditions and a higher quality of living environments, while maintaining the spirit of the social and cultural lifestyles of the past and possibly integrating them with the requirements of our time.